Comparing the effects of orthokeratology lenses and highly aspherical lenslets on axial length in myopic anisometropia - Minfeng Chen; Xianling Yang; Xibo Yu; Huihui Lei; Xinjie Mao (BMC Ophthalmology)
Abstract Purpose This study compares the influences of orthokeratology (OK) lenses and highly aspherical lenslets (HAL) on axial length (AL) in myopic anisometropia. Methods Retrospective analysis was performed on 225 individuals with myopic anisometropia who agreed to wear OK lenses, HAL or single-vision spectacles (SP). Subjects with bilateral myopic anisometropia (BMA) were divided into the following groups: SP-BMA, HAL-BMA and OK-BMA. Further, children with unilateral myopic anisometropia (UMA) were divided into the following groups: SP-UMA, UHAL-UMA (unilateral HAL), BHAL-UMA (bilateral HAL) and OK-UMA (unilateral OK lens). Analyzed the difference in the interocular AL elongation in different groups. Results For children with BMA, the interocular difference change in the OK-BMA group (0.15 ± 0.19 mm) was greater than that in the SP-BMA (−0.01 ± 0.20 mm) and HAL-BMA (−0.03 ± 0.17 mm) groups, all P < 0.001. For children with UMA, in the non-myopic eyes, the difference in AL elongation in the BHAL-UMA group (0.10 ± 0.14 mm) was less than that in the SP-UMA (0.28 ± 0.22 mm), UHAL-UMA (0.40 ± 0.22 mm) and OK-UMA (0.47 ± 0.24 mm) groups, all P < 0.001. The interocular change in the UHAL-UMA group (0.29 ± 0.36 mm) and OK-UMA group (0.35 ± 0.25 mm) were all higher than that in the SP-UMA (−0.02 ± 0.23 mm) and BHAL-UMA (0.01 ± 0.18 mm) groups, all P < 0.01. Conclusions OK lenses can effectively reduce the interocular AL difference for children with unilateral or bilateral myopic anisometropia. However, HAL only decreased the interocular AL difference for children with UMA when wearing unilateral HAL but it did slow down the AL elongation of the non-myopic eyes in children with UMA when wearing bilateral HAL.